Soil aridification, precipitations, and infant health: Evidence from Africa - Jacopo Lunghi; Maurizio Malpede; Marco Percoco (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2023)
This study shows how soil aridity (proxied with a measure of soil potential evapotranspiration) impacts child wellbeing in Sub-Saharan Africa. Using climate and infant health data from a grid of approximately 4,000 cells in 34 African countries, we find that infants born in arid areas are comparatively more likely to die under the age of 5 and be systematically underweight at birth. In addition, we show how the aridity measure in this study reduces the effect of rainfall on child wellbeing and how aridification drives substantial heterogeneity in the estimated response to increasing precipitation. The findings are combined with model projections of future climate conditions to emphasize the importance of accounting for aridity alongside precipitations when assessing the economic impact of climate.
Keywords: J1; J13; I15; Q54; Q56; O15; 330; Rainfall; climate change; potential evapotranspiration; child mortality; infant health